Magnetic material, preparation thereof, rotor and thermal management system

By covering the composite cladding layer on the surface of the magnetic alloy powder, the problem of performance attenuation of magnetic materials in water and oxygen environments is solved, and the effect of improving the processability and magnetic properties of magnetic materials is achieved.

CN119495483AActive Publication Date: 2025-02-21HANGZHOU QIANSHI TECH +1
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411603930.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-12
Publication Date
2025-02-21
Estimated Expiration
2044-11-12

AI Technical Summary

Technical Problem

Existing magnetic materials are susceptible to erosion of water and oxygen in processing and use environments, resulting in attenuation of magnetic properties and processing properties.

Method used

The magnetic alloy powder surface is coated with a composite cladding layer, including a porous phosphate as the first cladding layer and polycatechol ethylamine as the second cladding layer. The second cladding layer is at least partially interspersed and polymerized to be fixed in the pore structure of the first cladding layer to form a dense composite cladding layer.

Benefits of technology

Effectively isolate the erosion of water and oxygen, improve the processability, magnetic properties, mechanical properties and environmental stability of magnetic materials, and meet the injection molding needs of magnets in the thermal management system of new energy vehicles.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119495483A_ABST
    Figure CN119495483A_ABST
Patent Text Reader

Abstract

The invention discloses a magnetic material and preparation thereof, a rotor and a thermal management system, at least part of the surface of the magnetic material is coated with a composite coating layer, the composite coating layer comprises a first coating layer containing a-P (O)-structural fragment and a second coating layer containing a # imgabs0 # structural fragment, and the magnetic material is powdery; the magnetic material can be processed into a granular magnetic composite material, and comprises a magnetic material, a resin polymer bonding layer and a high-molecular elastomer, and the high-molecular elastomer is positioned among particles of the powdery magnetic material and is jointly dispersed in the resin polymer layer together with the particles of the powdery magnetic material. The magnetic material disclosed by the invention can be applied to a rotor and a thermal management system. The problem of performance degradation of related magnetic materials in the processing and using process is effectively solved, meanwhile, the processability, the magnetic performance, the mechanical performance and the environmental stability of the magnetic materials are improved, and the using requirements of magnets related to a new energy automobile heat management system can be met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of bonded magnetic materials, and in particular to magnetic materials and preparation methods thereof, rotors and thermal management systems. Background Art

[0002] With the rapid development of the manufacturing industry, China's automobile industry is facing the challenges of industrial transformation, emission reduction, energy crisis and low-carbon development. The development of new energy vehicles has become an important way to reduce the dependence on oil and exhaust pollution in the automobile industry. Since the engine, gearbox and other components of new energy vehicles have become batteries, motors, electronic controls and reducers, the magnets in the key components of the thermal management system are made of magnetic materials, and the thermal management system has high requirements for the comprehensive performance of magnetic materials.

[0003] Since magnetic materials are easily corroded by water and oxygen in the processing and use environment, resulting in the attenuation of magnetic properties and processing performance, and in the related art, magnetic materials still have the problem of easy attenuation of magnetic properties and processing performance. Therefore, it is urgent to improve the existing magnetic materials. Summary of the invention

[0004] The first object of the present invention is to provide a magnetic material in view of the shortcomings of the prior art, wherein a composite coating layer is coated on at least part of the surface of a magnetic alloy powder;

[0005] The composite coating layer comprises a first coating layer containing a -P(O)- structural segment and a first coating layer containing The second coating layer of the structural segment, the -P(O)- structural segment is connected to the metal atoms on the surface of the magnetic alloy powder by chemical bonds.

[0006] Furthermore, the first coating layer is a porous structure; further, the second coating layer is coated on the outside of the first coating layer, and at least partially penetrates, polymerizes and is fixed in the pore structure of the first coating layer.

[0007] Furthermore, the material of the first coating layer is phosphate.

[0008] Furthermore, the material of the second coating layer is polycatecholethylamine.

[0009] Furthermore, the magnetic material is in powder form.

[0010] Furthermore, the magnetic alloy powder is selected from at least one of neodymium iron boron alloy powder, samarium iron nitrogen alloy powder and samarium cobalt alloy powder.

[0011] Furthermore, a magnetic composite material comprises the above-mentioned magnetic material and a bonding layer, wherein the bonding layer is coated on at least a portion of the surface of the magnetic material; the bonding layer comprises a resin polymer and a high molecular weight elastomer dispersed in the resin polymer.

[0012] Furthermore, the content of the magnetic material is 83-93 wt.%, and the content of the bonding layer is 7-17 wt.%.

[0013] Furthermore, the resin polymer is polyphenylene sulfide or polyamide.

[0014] Furthermore, the polymer elastomer is located between particles of the magnetic material and is dispersed together with the particles of the magnetic material in the resin polymer bonding layer.

[0015] Furthermore, the polymer elastomer is selected from at least one of ethylene propylene diene monomer rubber grafted with glycidyl methacrylate and hydrogenated styrene-butadiene block copolymer grafted with glycidyl methacrylate.

[0016] Furthermore, the magnetic composite material is in granular form.

[0017] A second object of the present invention is to provide a method for preparing the above-mentioned magnetic material, comprising the following steps:

[0018] A compound containing a -P(O)- structural fragment is dissolved in an organic solvent, which may be ethanol, isopropanol, or a mixture of the two; a magnetic powder is immersed therein, stirred evenly so that it is fully in contact with the solution, immersed at room temperature for 1 to 24 hours, and then dried in a vacuum or non-reactive protective atmosphere to obtain a magnetic alloy powder coated with a first coating layer (porous phosphate), wherein the -P(O)- structural fragment is chemically bonded to the metal atoms on the surface of the magnetic alloy powder.

[0019] will contain The small molecule compound of the group is dissolved in an aqueous solution to obtain a precursor solution; the magnetic alloy powder material covered with the first coating layer is immersed in the precursor solution, stirred for 0.5 to 12 hours, the temperature is maintained at 40 to 60° C., and triethanolamine or ammonia water is added dropwise to maintain the pH value at 7.2 to 10.5; the powder is filtered and washed with an organic solvent such as ethanol or isopropanol to remove moisture, and then dried under vacuum or non-reactive protective atmosphere to obtain a magnetic alloy powder material covered with a second coating layer (polycatecholethylamine), wherein the coating layer contains The small molecule compound of the group enters the pore structure of the first coating layer and polymerizes therein to form a polycatechol ethylamine macromolecular compound, so that after the polymerization is completed, at least part of the second coating layer is inserted and fixed in the pore structure of the first coating layer, and fills and blocks the pore structure of the first coating layer to make it dense. Thus, the magnetic material of the present invention is obtained.

[0020] The magnetic material of the present invention (i.e., magnetic alloy powder with at least a portion of the surface covered with a composite coating layer), resin polymer, high molecular weight elastomer, etc. are placed in a mixer in proportion and mixed evenly to form a mixture; the mixture is then added to a screw extruder for mixing and granulation, thereby obtaining the magnetic composite material.

[0021] A third object of the present invention is to provide a rotor comprising the above-mentioned magnetic material or the above-mentioned magnetic composite material.

[0022] A fourth object of the present invention is to provide a thermal management system, which includes at least one of a pump, a valve and a cooling device, and at least one of the pump, the valve and the cooling device includes the above-mentioned magnetic material or the above-mentioned magnetic composite material.

[0023] Compared with the prior art, the present invention has the following beneficial effects:

[0024] The present invention coats the outer layer of the magnetic alloy powder with a composite coating layer, wherein: the first coating layer is connected to the surface of the magnetic alloy powder by chemical bonds, providing a strong bonding strength, and is porous; the second coating layer is at least partially interlaced and polymerized and fixed in the pore structure of the first coating layer, thereby firmly combining with the first coating layer, and blocking the pore structure of the first coating layer to make it dense. This effectively solves the problem of attenuation of magnetic properties and processing performance during the processing and use of related magnetic materials. At the same time, the processability, magnetic properties, mechanical properties, and environmental stability of the magnetic material are improved, which can meet the injection molding use requirements of the magnets involved in the thermal management system of new energy vehicles. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 This is a schematic structural diagram of an embodiment of a magnetic material covered with a composite coating layer in the present application;

[0026] Figure 2 A schematic structural diagram of an embodiment of a magnetic composite material including a resin polymer bonding layer in the present application;

[0027] Explanation of the accompanying drawings: 1. Magnetic alloy powder; 2. First coating layer; 3. Second coating layer; 4. Magnetic material; 5. Resin polymer bonding layer; 6. High molecular weight elastomer. DETAILED DESCRIPTION

[0028] In order to make the purpose, technical scheme and advantages of the present application clearer, the technical scheme of the present application will be clearly and completely described below in conjunction with specific embodiments. Obviously, the described embodiments are part of the embodiments of the present application, rather than all of the embodiments. Based on the technical scheme provided by the present application and the given embodiments, all other technical schemes obtained by those skilled in the art without making creative work, all belong to the scope of protection of the present application. Those who do not specify specific conditions in the embodiment shall proceed according to normal conditions or conditions recommended by the manufacturer. Those who do not specify the manufacturer for reagents or instruments used in the present application are all conventional products that can be purchased commercially.

[0029] The endpoints and any values ​​of the ranges disclosed in this application are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range or the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges.

[0030] In the related technologies, magnetic materials are generally prone to corrosion by water and oxygen during extrusion processing, injection molding to prepare magnetic devices, and use environments, resulting in attenuation of magnetic properties, processing properties, mechanical strength, etc., which greatly limits their application in thermal management system magnets, especially new energy vehicle thermal management systems. In order to solve the above defects, a single phosphating protection measure is usually used to improve the antioxidant properties of magnetic alloy powders, but the phosphating protective film usually contains a porous structure, which makes it difficult to protect densely, and the compatibility of inorganic phosphates and organic resin bonding layers is poor, resulting in the deterioration of magnetic properties and processing properties; and the use of inorganic materials such as carbon fiber, glass fiber, and carbon nanotubes to enhance and modify the resin polymer bonding layer will also cause the processing performance of the magnetic material to deteriorate, and even the injection molding of the magnet cannot be completed.

[0031] The present application provides a magnetic material, a form of which is a magnetic material 4, such as Figure 1 As shown, it includes a magnetic alloy powder 1, a first coating layer 2 (covered on at least part of the surface of the magnetic alloy powder 1, porous), and a second coating layer 3 (covered outside the first coating layer 2, and at least partially inserted and fixed in the pore structure of the first coating layer), wherein:

[0032] The first coating layer 2 is a compound containing a -P(O)- structural fragment, and the second coating layer 3 is a compound containing Compounds of structural fragments; further, in some embodiments, the first coating layer is phosphate and the second coating layer is polycatecholethylamine.

[0033] In some embodiments, the first coating layer 2 and the second coating layer 3 are collectively referred to as a composite coating layer. The first coating layer is coated on at least part of the surface of the magnetic alloy powder, and the second coating layer is coated on at least part of the surface of the first coating layer and interspersed and fixed therein.

[0034] In some embodiments, the first coating layer 2 has a porous structure with pores, which increases the specific surface area of ​​the magnetic alloy powder and provides a fixed fulcrum for the second coating layer; the second coating layer 3 is at least partially interspersed and fixed in the pore structure of the first coating layer 2.

[0035] The present application provides a magnetic composite material in the form of particles, such as Figure 2 As shown, it includes magnetic material 4, resin polymer bonding layer 5, and polymer elastomer 6; the magnetic material 4 and the polymer elastomer 6 are dispersed in the resin polymer bonding layer 5. During the injection molding process, the polymer bonding layer plays a role in bonding the magnetic material, and the polymer elastomer plays a toughening role to improve the mechanics but does not affect the magnetic properties.

[0036] In the present application, the first coating layer containing the -P(O)- structural fragment compound, i.e., the phosphate layer, has good heat resistance and corrosion resistance, and is connected to the surface of the magnetic alloy powder 1 in the form of a strong chemical bond, which is very strong. Although it is porous and difficult to be dense, the porosity of the first coating layer increases the specific surface area of ​​the magnetic alloy powder 1, thereby making the first coating layer The compound of the -P(O)- structural fragment is interspersed and polymerized in the pores of the first coating layer containing the -P(O)- structural fragment, thereby forming a dense and firmly bonded composite coating layer. That is to say, on the one hand, the first coating layer containing the -P(O)- structural fragment compound is connected to the magnetic alloy powder 1 by chemical bonds, making the first coating layer very strong; on the other hand, the porosity of the first coating layer containing the -P(O)- structural fragment compound increases the specific surface area of ​​the magnetic alloy powder 1, making the first coating layer containing the -P(O)- structural fragment compound The compounds of the structural fragments are firmly interspersed and polymerized outside the magnetic alloy powder 1 and seal the pores of the first coating layer. The two cooperate to form a firm and dense composite coating layer, which effectively isolates the corrosion of water and oxygen and improves the performance and stability of the magnetic material.

[0037] In the present application, the chemical structural formula of polycatechol ethylamine is:

[0038] In some embodiments, the magnetic material can be in powder form, and at least part of the surface of the powdered magnetic alloy is covered with a composite coating layer; the magnetic material can also be in granular form, in the form of a magnetic composite material including a resin bonding layer and a polymer elastomer and presenting discrete particles, and the polymer elastomer is located between the powdered magnetic material particles and dispersed therewith in the resin bonding layer; the magnetic material can also be in block form, that is, a magnet, in a state where the particles are melted and reassembled into the required shape of the rotor and the thermal management system magnetic device.

[0039] In some embodiments, the content of the magnetic material 4 described in the present invention (magnetic alloy powder with a composite coating layer covered on at least part of its surface) is 83-93wt.%, specifically selected from 84wt.%, 84.5wt.%, 85wt.%, 85.5wt.%, 86.5wt.%, 87wt.%, 87.5wt.%, 88wt.%, 88.5wt.%, 89wt.%, 89.5wt.%, 90wt.%, 90.5wt.%, 91wt.%, 91.5wt.%, 92wt.%, 92.5wt.%, or other values ​​within the range, which can be selected according to actual needs and is not limited here.

[0040] In some embodiments, the content of the resin polymer layer 5 is 7 to 17 wt.%, specifically selected from 7.0 wt.%, 7.5 wt.%, 8 wt.%, 8.5 wt.%, 9 wt.%, 9.5 wt.%, 10 wt.%, 10.5 wt.%, 11 wt.%, 11.5 wt.%, 12 wt.%, 12.5 wt.%, 13 wt.%, 13.5 wt.%, 14 wt.%, 14.5 wt.%, 15 wt.%, 15.5 wt.%, 16 wt.%, 16.5 wt.%, 17 wt.%, or other values ​​within the range, which can be selected according to actual needs and is not limited here.

[0041] In some embodiments, the content of the polymer elastomer 6 is 0.3-2wt.%, and can be specifically selected from 0.3wt.%, 0.4wt.%, 0.5wt.%, 0.6wt.%, 0.7wt.%, 0.8wt.%, 0.9wt.%, 1.0wt.%, 1.2wt.%, 1.4wt.%, 1.6wt.%, 1.8wt.%, 2.0wt.%, or other values ​​within the range, which can be selected according to actual needs and is not limited here.

[0042] The present application also provides a method for preparing a magnetic material, comprising the following steps:

[0043] A compound containing a -P(O)- structural fragment is dissolved in an organic solvent, which may be ethanol, isopropanol, or a mixture of the two; a magnetic powder is immersed therein, stirred evenly so that it is fully in contact with the solution, immersed at room temperature for 1 to 24 hours, and then dried in a vacuum or non-reactive protective atmosphere, thereby obtaining a magnetic alloy powder material coated with a first coating layer (porous phosphate), wherein the -P(O)- structural fragment is chemically bonded to the metal atoms on the surface of the magnetic alloy powder.

[0044] will contain The small molecular compound of the group is dissolved in pure water to obtain a precursor aqueous solution; the magnetic alloy powder material covered with the first coating layer is immersed in the precursor aqueous solution, stirred for 0.5 to 12 hours, the temperature is maintained at 40 to 60° C., and triethanolamine or ammonia water is added dropwise to maintain the pH value at 7.2 to 10.5; the powder is filtered and washed with an organic solvent such as ethanol and then vacuum dried to obtain a magnetic alloy powder material covered with a second coating layer (polycatecholethylamine), wherein the coating layer contains The small molecular compound of the group enters the pore structure of the first coating layer and polymerizes therein to form a polycatechol ethylamine macromolecular compound, so that after the polymerization is completed, the second coating layer is at least partially inserted and fixed in the pore structure of the first coating layer, and fills and blocks the pore structure of the first coating layer to make it dense. Thus, the magnetic material is obtained.

[0045] The magnetic material obtained in the previous step (i.e., magnetic alloy powder with at least a portion of the surface covered with a composite coating layer), resin binder, polymer elastomer and other raw materials are placed in a mixer in proportion and mixed evenly to form a mixture; the mixture is added to a screw extruder for mixing and granulation, thereby obtaining the magnetic composite material.

[0046] In some embodiments, the first coating layer 2 includes a compound containing a -P(O)- structural fragment, and further, the compound containing a -P(O)- structural fragment is a phosphate; the second coating layer 3 includes a compound containing The compound of the structural fragment further comprises The compound of the structural fragment is polycatecholethylamine.

[0047] In this application, the chemical structural formula of polycatechol ethylamine is: The reaction route is as follows:

[0048]

[0049] In some embodiments, the composite coating layer includes a first coating layer 2 and a second coating layer 3, the first coating layer includes phosphate, and the second coating layer includes polycatecholethylamine; the first coating layer is coated on at least a portion of the surface of the magnetic alloy powder, and the second coating layer is coated outside the first coating layer, and at least a portion is interspersed and fixed in the first coating layer.

[0050] In the present application, the first coating layer containing -P(O)- structural fragment compounds, i.e., the phosphate layer, has good heat resistance and corrosion resistance, and is connected to the surface of the magnetic alloy powder 1 in the form of strong chemical structural fragment connection, which is very strong. Although it is porous and difficult to be dense, the first coating layer can make the containing The compounds of the -P(O)- structural fragments are interspersed, polymerized, and fixed in the pores, thereby forming a dense and strong composite coating layer. That is to say, on the one hand, the first coating layer containing the -P(O)- structural fragment compound is connected to the magnetic alloy powder 1 by the chemical structural fragment, making the first coating layer very strong; on the other hand, the porosity of the first coating layer containing the -P(O)- structural fragment compound increases the specific surface area of ​​the magnetic alloy powder 1 and makes the -P(O)- structural fragment compound The compound of the structural fragment is firmly bonded to the surface of the magnetic alloy powder 1 and blocks the pores of the first coating layer, thereby increasing the bonding strength of the second coating layer. The two cooperate to form a strong and dense composite coating layer, which effectively isolates the corrosion of water and oxygen, effectively improves the processing performance of the magnetic material, and reduces the attenuation of magnetic properties during processing and use; at the same time, the inorganic surface of the magnetic alloy powder becomes the organic surface of the second coating layer, thereby improving the compatibility of the magnetic alloy powder with the resin bonding layer.

[0051] In some embodiments, the content of phosphoric acid in the phosphoric acid solution is 0.5-3.0wt.%, specifically selected from 0.5wt.%, 0.6wt.%, 0.8wt.%, 1.0wt.%, 1.2wt.%, 1.4wt.%, 1.6wt.%, 1.8wt.%, 2.0wt.%, 2.2wt.%, 2.4wt.%, 2.8wt.%, 3.0wt.%, or other values ​​within the range, which can be selected according to actual needs and is not limited here.

[0052] In some embodiments, the solvent of the phosphoric acid solution is ethanol, specifically a phosphoric acid ethanol solution; the first coating layer is a porous phosphate coating layer, that is, the first coating layer containing a -P(O)- structural fragment compound.

[0053] In some embodiments, the mass ratio of the magnetic alloy powder to the ethanol phosphoric acid solution is 5:(0.5-3), and a first coating layer containing a -P(O)- structural fragment compound is formed on the surface of the powder. On the one hand, the first coating layer containing the -P(O)- structural fragment compound is connected to the magnetic alloy powder by chemical bonds, making the first coating layer very strong; on the other hand, the porosity of the first coating layer containing the -P(O)- structural fragment compound increases the specific surface area of ​​the magnetic alloy powder.

[0054] In some embodiments, the solvent of the catecholamine solution is water, specifically a catecholamine aqueous solution, wherein the mass ratio of the magnetic alloy powder having at least a portion of its surface covered with the first coating layer to the catecholamine solution is 5:(0.5-3).

[0055] In some embodiments, the content of catecholethylamine in the catecholethylamine solution is 2 to 10 wt.%, specifically selected from 3 wt.%, 4 wt.%, 5 wt.%, 6 wt.%, 7 wt.%, 8 wt.%, 9 wt.%, 10 wt.%, or other values ​​within the range, which can be selected according to actual needs and are not limited here; catecholethylamine is a natural catechol substance with many functional groups (hydroxyl, amino, catechol group, etc.) on the surface, which can self-polymerize under alkaline conditions to form polycatecholethylamine.

[0056] In some embodiments, the pH adjustment value ranges from 7.2 to 10.5, and can be specifically selected from 7.3, 7.5, 7.7, 7.9, 8.1, 8.3, 8.5, 8.7, 8.9, 9.1, 9.3, 9.5, 9.7, 9.9, 10.1, and 10.3, or other values ​​within the range. It can be selected according to actual needs and is not limited here.

[0057] In some embodiments, the method for preparing the magnetic composite material further comprises the following steps:

[0058] Provide resin polymers and high molecular elastomers;

[0059] The magnetic material of the present invention (i.e., magnetic alloy powder having at least a portion of its surface covered with a composite coating layer), a resin polymer, and a high molecular weight elastomer are placed in a mixer and mixed evenly to form a mixture;

[0060] The mixed material is added into a screw extruder, and after mixing and granulation, a magnetic composite material is formed.

[0061] It should be noted that “wt.%” in the present application is expressed as mass percentage or weight percentage; “part by weight” refers to the basic unit of measurement of the weight ratio of multiple components, and 1 part can represent any unit mass, for example, 1 part can be expressed as 1g, 1.8g, or 5g, etc.

[0062] In some embodiments, the resin polymer is selected from polyphenylene sulfide or polyamide; the polymer elastomer can be selected from at least one of ethylene propylene diene monomer rubber grafted with glycidyl methacrylate and hydrogenated styrene-butadiene block copolymer grafted with glycidyl methacrylate; the polymer elastomer modified by grafting with active groups can effectively reduce the interfacial tension between the raw materials, which is beneficial to the dispersion of the magnetic material and the elastomer of the present invention in the resin polymer layer, and improves the interfacial compatibility between the raw materials, thereby ensuring the mechanical properties of the magnetic material; so that it can meet the injection molding use requirements of the magnetic devices involved in the thermal management system, especially the thermal management system of new energy vehicles; in addition, the preparation method of the magnetic material of the present application can be obtained by immersion coating, mixing, kneading and granulating the surface of the magnetic alloy powder, with mild conditions, simple process, low equipment requirements, convenient operation and control, which is conducive to stable product quality and suitable for industrial mass production.

[0063] In some embodiments, when the resin binder is polyphenylene sulfide, the mixing temperature is 280-350°C, specifically selected from 290°C, 300°C, 310°C, 320°C, 330°C, 340°C, 350°C, or other values ​​within the range, which can be selected according to actual needs and is not limited here; when the resin binder is polyamide, the mixing temperature is 200-250°C, specifically selected from 200°C, 210°C, 220°C, 230°C, 240°C, 250°C, or other values ​​within the range, which can be selected according to actual needs and is not limited here.

[0064] The present application also provides a rotor, which can be made of a magnetic material 4, or a magnetic composite material including a magnetic material 4 (composed of a magnetic alloy powder 1, a first coating layer 2, and a second coating layer 3), a resin binder 5, and a polymer elastomer 6;

[0065] The first coating layer 2 includes a compound containing a -P(O)- structural fragment; the second coating layer 3 includes a compound containing The compound of the structural fragment is interspersed and polymerized and fixed in the pores of the first coating layer 2.

[0066] Further, the compound containing the -P(O)- structural fragment is a phosphate, containing The compound of the structural fragment is polycatecholethylamine.

[0067] In the present application, the first coating layer containing the -P(O)- structural fragment compound, i.e., the phosphate layer, has good heat resistance and corrosion resistance, and is connected to the surface of the magnetic alloy powder in the form of a strong chemical structural fragment connection, which is very strong. Although it is porous and difficult to be dense, the porosity of the first coating layer increases the specific surface area of ​​the magnetic alloy powder, thereby making the first coating layer The compound of the -P(O)- structural fragment is interspersed in the pores of the first coating layer containing the -P(O)- structural fragment, thereby forming a dense and strong composite coating layer. That is to say, on the one hand, the first coating layer containing the -P(O)- structural fragment compound is connected to the magnetic alloy powder by chemical bonds, making the first coating layer very strong; on the other hand, the porosity of the first coating layer containing the -P(O)- structural fragment compound increases the specific surface area of ​​the magnetic alloy powder, making the first coating layer containing the -P(O)- structural fragment compound The compound of the structural fragment is firmly bonded to the surface of the magnetic alloy powder and blocks the pores of the first coating layer. The two cooperate to form a strong and dense composite coating layer, which effectively isolates water and oxygen corrosion, thereby meeting the use requirements of magnets (such as rotors) involved in the thermal management system of new energy vehicles, especially new energy thermal management systems. It should be noted that this application is aimed at magnetic materials in thermal management systems, especially for the design of rotors in water pumps, oil pumps, throttle valves, water valves and cooling devices. The performance requirements of magnetic materials in thermal management systems are: (1) According to the GB / T3217-2013 test method, after high temperature accelerated environmental testing (300°C, 24h), the coercive force Hcj ≥ 8500 Oe; (2) According to the GB / T 3217-2013 test, the maximum magnetic energy product (BH) max ≥45kJ / m 3 ; (3) After high temperature environment test (150℃, 100h), magnetic moment attenuation ≤3%; (4) According to GB / T3682-2000 test method, under the test conditions of 310℃ and 10kg, melt index MFR ≥100g / 10min; (5) According to GB / T1040.2-2006, tensile strength ≥40MPa; (6) GB / T 9341-2008, flexural strength ≥50 MPa; (7) GB / T 1843-2008, impact strength ≥5.0 MPa; (8) No cracking in high and low temperature impact test.

[0068] In some embodiments, the magnetic alloy powder is a rare earth magnetic alloy powder selected from at least one of neodymium iron boron, samarium iron nitrogen and samarium cobalt, that is, one of them can be selected, or a plurality of composite magnetic alloy powders of neodymium iron boron, samarium iron nitrogen and samarium cobalt can be selected.

[0069] In some embodiments, the rotor further comprises a polymer elastomer, which may be selected from at least one of ethylene propylene diene monomer rubber grafted with glycidyl methacrylate and hydrogenated styrene-butadiene block copolymer grafted with glycidyl methacrylate.

[0070] It should be noted that the magnetic material in the present application can be in powder, granular, or block form, that is, a magnet; the magnet can be in various shapes, not limited to tile, disk, square, cylindrical, ring, etc.

[0071] The rotor in the present application can be made of magnetic materials through processes such as compression molding, injection molding, extrusion molding and calendering molding; the magnetic materials in the present application, such as magnets, can be used for rotors involved in thermal management systems, such as control components (electronic expansion valves, water valves, etc.), heat exchange components (cooling plates, coolers, oil coolers, etc.) and magnetic rotors in drive components (electronic water pumps and oil pumps, etc.), etc., which can meet the performance requirements of magnets in thermal management systems, such as magnetic properties, thermal stability, processing performance and mechanical properties of magnets.

[0072] The present application also provides a thermal management system, which includes at least one of a pump, a valve and a cooling device, wherein at least one of the pump, the valve and the cooling device can be made of a magnetic material 4, or a magnetic composite material including a magnetic material 4 (composed of a magnetic alloy powder 1, a first coating layer 2, a second coating layer 3), a resin binder 5, and a polymer elastomer 6; wherein,

[0073] The composite coating layer (the first coating layer 2, the second coating layer 3) includes a compound containing a -P(O)- structural fragment and a compound containing Structural fragment compounds.

[0074] In the present application, the thermal management component in the thermal management system includes at least one of a pump, a valve and a cooling device, at least one of the pump, the valve and the cooling device includes a magnetic material, and the magnetic material includes a magnetic alloy powder 1 at least part of the surface of which is covered with a first coating layer 2 and a second coating layer 3.

[0075] In some embodiments, the pump includes but is not limited to a water pump, an oil pump, etc., the valve includes but is not limited to a refrigerant valve, a water valve, etc., and the cooling device includes but is not limited to a cooling plate, a cooler, an oil cooler, etc.

[0076] In addition, it should be noted that the thermal management system in the present application mainly includes four parts: a battery thermal management system, an automotive air-conditioning system, a motor electronic control cooling system, and a reducer cooling system; further, the thermal management system of the present application is a new energy vehicle thermal management system. The new energy vehicle thermal management system is classified according to the cooling medium and mainly includes a liquid cooling circuit (cooling system for batteries and motors, etc.), an oil cooling circuit (cooling system for reducers, etc.) and a refrigerant circuit (air-conditioning system). The components involved include control components (electronic expansion valves, water valves, etc.), heat exchange components (cooling plates, coolers, oil coolers, etc.) and drive components (electronic water pumps and oil pumps, etc.). The magnets in the key components such as electronic expansion valves, water valves, electronic water pumps, oil pumps, cooling plates, coolers and oil coolers are made of magnetic materials, and the magnets can meet the use requirements of the thermal management system of new energy vehicles.

[0077] The present application is further described below by way of examples.

[0078] Example 1

[0079] A method for preparing a magnetic material comprises the following steps:

[0080] (a) A magnetic material coated with a phosphate-polycatecholethylamine composite coating layer is prepared by the following steps:

[0081] Step (I), dissolving phosphoric acid in an ethanol solvent, wherein the mass percentage of phosphoric acid is 1%; dissolving magnetic alloy powder (NdFeB alloy powder, coercivity Hcj: 9650Oe, maximum magnetic energy product (BH) max: 122kJ / m 3 ) is immersed therein, the mass ratio of magnetic alloy powder to phosphoric acid ethanol mixed solution is 5:2; it is stirred evenly to make it fully contact with the solution, and after soaking at room temperature for 5 hours, vacuum drying is performed to obtain a magnetic powder covered with a first coating layer (porous phosphate).

[0082] Step (II), dissolving catecholethylamine in pure water to obtain a precursor solution, wherein the mass percentage of catecholethylamine is 4%; immersing the magnetic alloy powder material covered with the first coating layer after the treatment in step (i) therein, wherein the mass ratio of the magnetic alloy powder to the catecholethylamine solution is 5:2, stirring for 5 hours while maintaining the temperature at 40-60°C, and adding triethanolamine dropwise to adjust the pH value to about 8.9; then filtering and washing with an organic solvent such as ethanol to remove the residual precursor aqueous solution, and then vacuum drying to obtain a magnetic alloy powder material covered with a second coating layer (polycatecholethylamine).

[0083] (b) The magnetic composite material is obtained by the following steps:

[0084] Step (III), 90 parts of the magnetic material coated with the composite coating layer obtained in step (a), 9 parts of a polyphenylene sulfide resin binder, and 1 part of a polymer elastomer (ethylene propylene diene monomer rubber grafted with glycidyl methacrylate) are placed in a high-speed mixer and mixed evenly to obtain a mixture;

[0085] Step (IV), adding the mixed material into a twin-screw extruder, mixing and granulating at 320°C to obtain a granular magnetic composite material.

[0086] Example 2

[0087] A method for preparing a magnetic material, compared with Example 1, the difference is that: in step (I), the mass percentage of phosphoric acid is 2%, and the mass ratio of magnetic alloy powder to phosphoric acid ethanol mixed solution is 5:1.2; in step (II), the mass percentage of catecholethylamine is 8%, and the mass ratio of magnetic alloy powder to catecholethylamine solution is 5:1; the remaining steps are the same.

[0088] Example 3

[0089] A method for preparing a magnetic material, compared with Example 1, the difference is that: in step (II), triethanolamine is added dropwise to adjust the pH value to about 7.8; the remaining steps are the same.

[0090] Example 4

[0091] A method for preparing a magnetic material, compared with Example 1, the difference is that: the mixture ratio of step (III) is 90 parts of the magnetic alloy powder coated with a composite coating layer obtained in step (a), 8.5 parts of a polyphenylene sulfide resin binder, and 1.5 parts of a polymer elastomer (ethylene propylene diene monomer rubber grafted with glycidyl methacrylate); the remaining steps are the same.

[0092] Comparative Example 1

[0093] A method for preparing a magnetic material, compared with Example 1, the difference is that the process of preparing a composite coating layer on the surface of a magnetic alloy powder in step (a) is omitted, and the remaining steps are exactly the same as in Example 1; that is, steps (I) and (II) are omitted, and steps (III) and (IV) are directly performed to prepare a granular magnetic composite material.

[0094] Comparative Example 2

[0095] A method for preparing a magnetic material, compared with Example 1, the difference is that in step (a), a first phosphate coating layer is prepared on the surface of a magnetic alloy powder but a second coating layer is not prepared, and the remaining steps are exactly the same as in Example 1; that is, after performing step (I) to prepare the first coating layer on the surface of the magnetic alloy powder, step (II) in step (a) is omitted, and steps (III) and (IV) are directly performed to prepare a granular magnetic composite material.

[0096] Comparative Example 3

[0097] A method for preparing a magnetic material, compared with Example 1, the difference is that in step (a), a second polycatecholamine coating layer is directly performed on the surface of a magnetic alloy powder without preparing a first phosphate coating layer, and the remaining steps are exactly the same as in Example 1; that is, step (I) in step (a) is omitted, and step (II) in step (a), and step (III) and step (IV) in step (b) are directly performed to prepare a granular magnetic composite material.

[0098] Comparative Example 4

[0099] A method for preparing a magnetic material, compared with Example 1, the difference is that: the mixture ratio of step (III) is 90 parts of the magnetic alloy powder coated with a composite coating layer obtained in step (a), 10 parts of a polyphenylene sulfide resin binder, and 0 parts (i.e., no addition) of a polymer elastomer (ethylene propylene diene monomer rubber grafted with glycidyl methacrylate); the remaining steps are the same.

[0100] Test Example 1

[0101] The specific surface area of ​​the powdered magnetic material obtained in step (I) and step (II) in step (a) of Examples 1 to 4 and Comparative Examples 1 to 3 was measured by static volumetric method, and the unit is m 2 / g.

[0102] The coercivity performance Hcj test was performed on the powdered magnetic material obtained in step (a) and the granular magnetic composite material obtained in step (b) in Examples 1 to 4 and Comparative Examples 1 to 3. The test standard is in accordance with GB / T 3217-2013, and the unit is Oe. The coercivity values ​​of the powdered magnetic material and the granular magnetic composite material after being placed under high temperature conditions for a certain period of time (300°C, 24 hours) were tested, and the degree to which the material resisted coercivity attenuation was judged by the difference. The coating process of the surface coating layer of the magnetic alloy powder material in Comparative Example 4 is the same as that in Example 1, so the relevant data of Comparative Example 4 are not listed in Table 1.

[0103] Table 1 Specific surface area and coercivity test results

[0104]

[0105]

[0106] As can be seen from Table 1, by comparing Examples 1 to 4 with Comparative Examples 1 to 3, it can be seen that the coercivity index of the powdered magnetic material obtained in step (I) of Examples 1 to 3 and the granular magnetic composite material obtained in step (II) is significantly better than that of Comparative Examples 1 to 3 in resisting environmental aging test (300°C, 24 hours), which indicates that the magnetic alloy powder magnetic material containing a composite coating layer in the present application can maintain better magnetic properties after experiencing a harsh environment. In addition, by comparing Comparative Example 1 with Example 1, it can be concluded that the magnetic alloy powder without a composite coating layer performs the worst as a raw material, and the coercivity performance is significantly attenuated after the aging test; by comparing Comparative Examples 2 and 3 with Example 1, it can be concluded that the magnetic alloy powder with a single first coating layer (i.e., phosphate coating layer) or a second coating layer (i.e., polycatechol ethylamine coating layer) as a raw material has a certain effect, but it is obviously not as good as the effect of coating a composite coating layer. In order to analyze the reason, by comparing the specific surface area of ​​the powders obtained in step (I) and step (II) in step (a), and comparing with the specific surface area of ​​the magnetic alloy powder raw material, it can be seen that: on the one hand, the specific surface area of ​​the powder obtained in step (I) is significantly higher than the specific surface area of ​​the original magnetic alloy powder, indicating that the first coating layer contains a porous structure, thereby increasing the specific surface area of ​​the powder material. In this process, the first coating layer containing the -P(O)- structural fragment compound is firmly connected to the magnetic alloy powder by chemical bonds; on the other hand, the specific surface area of ​​the powder obtained in step (II) is restored to be very close to the specific surface area of ​​the original magnetic alloy powder, indicating that this process contains The compounds of the structural fragments are firmly interspersed, polymerized, and fixed inside and outside the pores of the first coating layer on the surface of the magnetic alloy powder, and the pores are blocked; the two work together to form a strong and dense composite coating layer, which effectively isolates the erosion of water, oxygen, etc. in the environment, and improves the stability of the coercive force performance of the magnetic material.

[0107] Test Example 2

[0108] The granular magnetic composite materials obtained in step (b) of Examples 1 to 4 and Comparative Examples 1 to 3 were tested and characterized, and the corresponding test methods and sample preparation conditions are shown in Table 2. Maximum Magnetic Energy Product (BH) maxThe test methods of melt index MFR, tensile strength, bending strength and impact strength refer to the corresponding national standards in Table 2 respectively; the magnetic moment decay is measured by testing the magnetic moment value of the φ10×10mm cylinder (same as the maximum magnetic energy product test sample cylinder) after magnetization saturation and the magnetic moment decay value after placing it in a 150℃ environment for 100h; the test of high and low temperature impact cracking rate refers to the rapid switching of 10 metal shaft ring rotors with an outer diameter of 12mm and an inner diameter of 4mm between -40℃ and 150℃ for temperature shock, keeping each temperature for 2h to fully reach the corresponding temperature, and quickly transferring it to another temperature for 2h, and observing the number of cracks in the 10 samples after 500 cycles. The test results are shown in Table 3.

[0109] Table 2 Test methods and sample preparation conditions

[0110]

[0111] Table 3 Test results

[0112]

[0113] As can be seen from Table 3, by comparing Comparative Examples 1 to 4 with Examples 1 to 4, it can be seen that the magnetic material of the present invention has a higher maximum magnetic energy product, a lower magnetic moment attenuation, and better mechanical properties, and no cracking is found in the high and low temperature impact cycle test after being made into a rotor magnetic device, which meets the use requirements of injection molded magnets involved in the thermal management system of new energy vehicles. Among them: By comparing Comparative Example 1 with Examples 1 to 4, it can be seen that the magnetic material without a composite coating layer on the surface of the magnetic alloy powder is easily damaged during the processing, so (BH) max , MFR, and mechanical strength are all low, and the magnetic moment decays more after the high-temperature accelerated environmental test. Even if a polymer elastomer (ethylene propylene diene monomer rubber grafted with glycidyl methacrylate) is added to the resin bonding layer, there is still a cracking ratio after the high and low temperature impact cycle test; Comparative Example 2 is compared with Examples 1 to 4 to show that the magnetic material with a single first coating layer (phosphate coating layer) coated on the surface of the magnetic alloy powder has a certain improvement effect, but is not as good as the present application, because the phosphate coating layer has a porous structure that is not dense enough, and has poor compatibility with the organic resin bonding layer, so (BH) max, MFR, and mechanical strength are still lower than those of the embodiment, and the magnetic moment decay after the high temperature accelerated environmental test is also higher than that of the embodiment. Even if a polymer elastomer (ethylene propylene diene monomer rubber grafted with glycidyl methacrylate) is added to the resin bonding layer, there is still a cracking ratio after the high and low temperature impact cycle test; Comparison of Example 3 with Examples 1 to 4 shows that the magnetic material with a single second coating layer (polycatecholethylamine coating layer) on the surface of the magnetic alloy powder has a certain improvement effect, but is not as good as the present application. Although the polycatecholethylamine coating layer has good compatibility with the organic resin bonding layer, it lacks the first coating layer containing a porous structure as a fulcrum for polymerization and interlacing and fixing therein, and is therefore easily peeled off from the surface of the magnetic alloy powder during processing and shearing, resulting in (BH) max , MFR, and mechanical strength are still lower than those of the examples. The magnetic moment decay after the high temperature accelerated environmental test is also higher than that of the examples. Even if a polymer elastomer (ethylene propylene diene monomer rubber grafted with glycidyl methacrylate) is added to the resin bonding layer, there is still a cracking ratio after the high and low temperature impact cycle test. Comparison of Comparative Example 4 with Examples 1 to 4 shows that since the surface of the magnetic alloy powder is covered with the same composite coating layer as in the examples, (BH) max The performances in terms of MFR, magnetic moment attenuation after high-temperature accelerated environmental testing are comparable to those in the examples. However, since there is no polymer elastomer (ethylene propylene diene monomer rubber grafted with glycidyl methacrylate) in the resin binder layer to play a toughening role, there is a cracking ratio after the high and low temperature impact cycle test.

[0114] like Figure 1 As shown, the powdered magnetic material prepared in the present application has a magnetic alloy powder magnetic alloy particle-composite coating layer structure, and the composite coating layer includes a first coating layer (containing a -P(O)- structure fragment coating layer) and a second coating layer (containing The first coating layer has a pore structure and is connected to the magnetic alloy powder by chemical bonds, providing a strong bonding strength. The second coating layer is at least partially interspersed and polymerized and fixed in the pore structure of the first coating layer, firmly connected to the first coating layer, and blocks the pore structure of the first coating layer to make it dense. This effectively solves the problem of attenuation of magnetic properties and processing performance during the processing and use of magnetic materials. Further, if Figure 2 As shown, the granular magnetic composite material prepared in this application is Figure 1 After the powdered magnetic material is mixed with a resin binder and a polymer elastomer, the material has excellent magnetic properties, flow characteristics (MFR), mechanical strength, and resistance to magnetic moment decay and high and low temperature impact. Magnetic alloy powders are well used in magnets involved in control components (electronic expansion valves, water valves, etc.), heat exchange components (cooling plates, coolers, oil coolers, etc.) and drive components (electronic water pumps and oil pumps, etc.) of the thermal management system of new energy vehicles.

[0115] The above implementation modes are only used to illustrate the present application and are not intended to limit the technical solutions described in the present application. The understanding of the present application should be based on the technical personnel in the relevant technical field. Although the present application has been described in detail in this specification with reference to the above implementation modes, ordinary technical personnel in the field should understand that the technical personnel in the relevant technical field can still modify or make equivalent substitutions to the present application, and all technical solutions and improvements thereof that do not depart from the spirit and scope of the present application should be included in the scope of the claims of the present application.

Claims

1. A magnetic material, characterized in that: The magnetic material is a composite coating layer coated on at least part of the surface of a magnetic alloy powder; wherein, The composite coating layer comprises a first coating layer containing a -P(O)- structural segment and a first coating layer containing The second coating layer of the structural segment, the -P(O)- structural segment is connected to the metal atoms on the surface of the magnetic alloy powder by chemical bonds.

2. The magnetic material according to claim 1, characterized in that: The first coating layer is a porous structure; the second coating layer is coated on the outside of the first coating layer, and at least partially interspersed and polymerized and fixed in the pore structure of the first coating layer; the material of the first coating layer is phosphate, and the material of the second coating layer is polycatecholethylamine.

3. The magnetic material according to claim 1, characterized in that: The magnetic material is in powder form; the magnetic alloy powder is selected from at least one of neodymium iron boron alloy powder, samarium iron nitrogen alloy powder and samarium cobalt alloy powder.

4. A magnetic composite material, comprising the magnetic material according to any one of claims 1 to 3 and a bonding layer, wherein the bonding layer is coated on at least a portion of the surface of the magnetic material; the bonding layer comprises a resin polymer and a high molecular weight elastomer dispersed in the resin polymer.

5. The magnetic composite material according to claim 4, characterized in that: The magnetic composite material is in granular form; in the magnetic composite material, the content of the magnetic material is 83-93 wt.%, and the content of the bonding layer is 7-17 wt.%.

6. The magnetic composite material according to claim 5, characterized in that: In the bonding layer, the resin polymer is polyphenylene sulfide or polyamide, and the high molecular weight elastomer is selected from at least one of ethylene propylene diene monomer rubber grafted with glycidyl methacrylate and hydrogenated styrene-butadiene block copolymer grafted with glycidyl methacrylate.

7. A method for preparing a magnetic material according to any one of claims 1 to 3, characterized in that: The preparation method comprises the following steps: The compound containing the -P(O)- structural fragment is dissolved in an organic solvent, and the magnetic alloy powder is immersed therein, stirred evenly so that it is fully in contact with the solution, immersed at room temperature for 1 to 24 hours, and then dried in a vacuum or non-reactive protective atmosphere to obtain a magnetic alloy powder covered with a first coating layer; will contain The small molecule compound of the group is dissolved in water to obtain a precursor solution; the magnetic alloy powder covered with the first coating layer is immersed in the precursor solution, stirred at 40 to 60° C. for 0.5 to 12 hours, and triethanolamine or ammonia water is added dropwise to maintain the pH value at 7.2 to 10.5; after the reaction is completed, the solution is filtered and washed to remove moisture, and dried under vacuum or non-reactive protective atmosphere to obtain the magnetic material.

8. A method for preparing the magnetic composite material according to any one of claims 4 to 6, characterized in that: The preparation method comprises the following steps: The magnetic material, the resin polymer and the high molecular weight elastomer are mixed uniformly to form a mixture; the mixture is then added into a screw extruder for mixing and granulation to obtain the magnetic composite material.

9. A rotor, characterized in that: The rotor comprises the magnetic material according to any one of claims 1 to 3 or the magnetic composite material according to any one of claims 4 to 6.

10. A thermal management system, comprising at least one of a pump, a valve and a cooling device, characterized in that: At least one of the pump, the valve and the cooling device comprises the magnetic material according to any one of claims 1 to 3 or the magnetic composite material according to any one of claims 4 to 6.

Citation Information

Patent Citations

  • Environment-friendly halogen-free rare-earth composite magnetic material

    CN102832002A

  • High-performance polyphenyl thioether / samarium-iron-nitrogen magnetic composite material and preparation method thereof

    CN106317875A

  • Nano multipolymer for modification of injection molding magnetic material and preparation method of nano multipolymer

    CN106893313A

  • Rare earth composite material and preparation method and application thereof

    CN114381122A

  • Soft magnetic powder core and preparation method and application thereof

    CN115762946A